Immune Evasion Mechanism and AXL - Son, Hye-Youn; Jeong, Hwan-Kyu (Frontiers in Oncology, 2021)
Extensive interest in cancer immunotherapy is reported according to the clinical importance of CTLA-4 and (PD-1/PD-L1) [programmed death (PD) and programmed death-ligand (PD-L1)] in immune checkpoint therapies. AXL is a receptor tyrosine kinase expressed in different types of cancer and in relation to resistance against various anticancer therapeutics due to poor clinical prognosis. AXL and its ligand, i.e., growth arrest-specific 6 (GAS6) proteins, are expressed on many cancer cells, and the GAS6/AXL pathway is reported to promote cancer cell proliferation, survival, migration, invasion, angiogenesis, and immune evasion. AXL is an attractive and novel therapeutic target for impairing tumor progression from immune cell contracts in the tumor microenvironment. The GAS6/AXL pathway is also of interest immunologically because it targets fewer antitumor immune responses. In effect, several targeted therapies are selective and nonselective for AXL, which are in preclinical and clinical development in multiple cancer types. Therefore, this review focuses on the role of the GAS6/AXL signaling pathway in triggering the immunosuppressive tumor microenvironment as immune evasion. This includes regulating its composition and activating T-cell exclusion with the immune-suppressive activity of regulatory T cells, which is related to one of the hallmarks of cancer survival. Finally, this article discusses the GAS6/AXL signaling pathway in the context of several immune responses such as NK cell activation, apoptosis, and tumor-specific immunity, especially PD-1/PDL-1 signaling.